2016
DOI: 10.1371/journal.pone.0163120
|View full text |Cite
|
Sign up to set email alerts
|

CD11c/CD18 Dominates Adhesion of Human Monocytes, Macrophages and Dendritic Cells over CD11b/CD18

Abstract: Complement receptors CR3 (CD11b/CD18) and CR4 (CD11c/CD18) belong to the family of beta2 integrins and are expressed mainly by myeloid cell types in humans. Previously, we proved that CR3 rather than CR4 plays a key role in phagocytosis. Here we analysed how CD11b and CD11c participate in cell adhesion to fibrinogen, a common ligand of CR3 and CR4, employing human monocytes, monocyte-derived macrophages (MDMs) and monocyte-derived dendritic cells (MDDCs) highly expressing CD11b as well as CD11c. We determined … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
81
0
5

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 77 publications
(95 citation statements)
references
References 54 publications
9
81
0
5
Order By: Relevance
“…Though both CR3 and CR4 are able to bind fibrinogen and iC3b, we found that either of them dominates the other in various functions, such as antigen uptake, digestion, in addition to adhesion and spreading, which we had shown earlier (Sándor, 2016).…”
Section: Discussionsupporting
confidence: 66%
“…Though both CR3 and CR4 are able to bind fibrinogen and iC3b, we found that either of them dominates the other in various functions, such as antigen uptake, digestion, in addition to adhesion and spreading, which we had shown earlier (Sándor, 2016).…”
Section: Discussionsupporting
confidence: 66%
“…The CD11b, CD11c and CD18 leukointegrins play a role in phagocytosis, cell‐to‐cell and cell‐to‐extracellular matrix . Our data indicate similarity with those in the literature, where reports have shown that L. chagasi infection induces decreased expression of CD11b/CD18 in macrophages .…”
Section: Discussionsupporting
confidence: 89%
“…Although CR3 and CR4 were thought to exert similar functions, recently we showed that they have different roles in various human myeloid cells. Namely, while CR3 dominates phagocytosis in the case of dendritic cells [3], CR4 is more important in mediating adherence by human monocytes macrophages and dendritic cells [2].…”
Section: Introductionmentioning
confidence: 97%
“…These receptors mediate several important cellular functions, including adhesion, trans-endothelial migration and interaction with extracellular matrix proteins [1]. By interaction with iC3b, the complement-derived natural ligand, CR3 and CR4 mediate the uptake of opsonized cells and particles by monocytes, macrophages, neutrophils and dendritic cells [2]. Although CR3 and CR4 were thought to exert similar functions, recently we showed that they have different roles in various human myeloid cells.…”
Section: Introductionmentioning
confidence: 99%